PENGARUH PEMBERIAN THERAPI TOMAT TERHADAP PENURUNAN TEKANAN DARAH PASIEN DENGAN HIPERTENSI DI PUSKESMAS KERINJING - NEN SASTRI (LPPM STIKes Mitra Adiguna, 2023)
Hypertension has resulted in the death of around 8 million each year, 1.5 million deaths occur in Southeast Asia where a third of the population suffers from hypertension. Objective: To determine the effect of giving 150 grams of tomatoes on the blood pressure value of hypertensive patients. Methods: The design of this study used a quasi-experimental design, namely the pre and post test approach without a control group. Population: the sample is selected by purposive sampling according to predetermined criteria. The research was conducted to 17 respondents. Case criteria are all suspected patients with hypertension who are not and or are currently taking hypertension medication. Research instruments: Tools and materials: tomatoes, blender, scales, sphygmomanometer (sphygmomanometer). Choose fresh red tomatoes, weigh the tomatoes weighing 150 grams, then put them in a blender, given with a dose of 2 times a day. The collected data were then analyzed using a paired t-test. Results: the average systolic blood pressure before being given tomatoes was 174.24 mmHg with the lowest number being 140 mmHg and the highest being 259 mmHg, while the average systolic blood pressure after the intervention was 158.06 with the lowest number being 121 mmHg and the highest being 256 mmHg. The average diastolic blood pressure before the intervention was 98.82 with the lowest value being 73 mmHg and the highest being 146 mmHg, while the average diastolic blood pressure after the intervention was 92.18 with the lowest value being 62 mmHg and the highest being 136 mmHg. Conclusion: there is a significant difference between systolic blood pressure before and after giving tomato therapy to hypertensive patients with a p value = 0.001 and there is a significant effect on diastolic blood pressure before and after giving tomatoes to hypertensive patients with a p value = 0.042. Suggestion: it is recommended that sodium intake should be limited to <100 mmol (2 grams) / day equivalent to 5 grams. Keywords: Tomato therapy, pre test, post test, hypertension, blood pressure